Effects of Nerve Growth Factor-β From Bull Seminal Plasma on Steroidogenesis and Angiogenic Markers of the Bovine Pre-ovulatory Follicle Wall Cell Culture - Stewart, Jamie L.; Gao, Liying; Flaws, Jodi A.; Mercadante, Vitor R. G.; Dias, Nicholas W.; Canisso, Igor F.; Lima, Fabio S. (Frontiers in Veterinary Science, 2022)
Nerve growth factor-β (NGF) is critical for ovulation in the mammalian ovary and is luteotrophic when administered systemically to camelids and cattle. This study aimed to assess the direct effects of purified bovine NGF on steroidogenesis and angiogenic markers in the bovine pre-ovulatory follicle. Holstein heifers (n=3) were synchronized with a standard protocol and heifers with the preovulatory follicle (≥ 12 mm) had an the ovary containing the dominant follicle removed via colpotomy. Pre-ovulatory follicles were dissected in 24 pieces containing theca and granulosa cells that were randomly allocated to receive either cultured in media supplemented with purified bovine NGF (100 ng/mL) or untreated (control) for 72 h. The supernatant media was harvested for determination of progesterone, testosterone, and estradiol, whereas explants were used for mRNA analyses for steroidogenesis and angiogenic markers.Treatment of follicle wall cells with NGF upregulated gene expression of steroidogenic enzyme HDS17B (P = 0.04) and increased testosterone production (P < 0.01). However, NGF treatment did not alter production of progesterone (P = 0.81) or estradiol (P = 0.14). Consistently, gene expression of steroidogenic enzymes responsible for producing these hormones (STAR, CYP11A1, HSD3B, CYP17A1, CYP19A1) were unaffected by NGF treatment (P ≥ 0.31). Treatment with NGF downregulated gene expression of the angiogenic enzyme FGF2 (P = 0.02) but did not alter PGES (P = 0.63), VEGFA (P = 0.44), and ESR1 (P = 0.77). Collectively, these results demonstrate that NGF from seminal plasma may interact directly with the bovine pre-ovulatory follicle to alter downstream steroidogenesis and luteal development.